Analysis of the transverse compressive behavior of Kevlar fibers using microscopic scale approach. (December 2019) - Hoan-Pham, Q.; Ha-Minh, C.; Long-Chu, T.; Kanit, T.; Imad, A.
Highlights: Microscopic numerical investigation of the transverse compressive behavior of single and bulk aramid fibers. Numerical calculations in the case of a transverse compression using the assumption of plane strain and validated by experimental data. Variation of the transverse mechanical effective property versus fiber volume fraction using numerical homogenization technique. A power relationship describing effective transverse Young's modulus E ¯ and apparent strain ε ¯ versus the normalized fiber volume fraction has been proposed. Abstract: During the ballistic impact process of fabrics, yarns are locally subjected to both longitudinal tensile and transverse compressive loading. This paper presents a microscopic numerical investigation of the transverse compressive behavior of a single and bulk aramid fibers. Interactions with friction between single fibers in a yarn have been taken into account. Numerical calculations were performed in the case of a transverse compression using the assumption of plane strain and validated by experimental data. Effects of friction and representative volume size were also discussed. It can be highlighted that using a numerical homogenization technique, the variation of the transverse mechanical effective property versus fiber volume fraction has been determined based on the microscopic transverse behavior of bulk aramid fibers. Finally, power relationships describing effective transverse Young's modulus E ¯ and apparent strain ε ¯ versus the normalized fiber volume fraction have been proposed and discussed. This effective homogenized material allows the development of homogenized Kevlar yarns and fabrics in the further works of homogenized approaches.